Modern management of anal fistula - Limura, Elsa (World journal of gastroenterology : WJG, 2015)
Ideal surgical treatment for anal fistula should aim to eradicate sepsis and promote healing of the tract,whilst preserving the sphincters and the mechanism of continence.For the simple and most distal fistulae,conventional surgical options such as laying open of the fistula tract seem to be relatively safe and therefore,well accepted in clinical practise.However,for the more complex fistulae where a significant proportion of the anal sphincter is involved,great concern remains about damaging the sphincter and subsequent poor functional outcome,which is quite inevitable following conventional surgical treatment.For this reason,over the last twodecades,many sphincter-preserving procedures for the treatment of anal fistula have been introduced with the common goal of minimising the injury to the anal sphincters and preserving optimal function.Among them,the ligation of intersphincteric fistula tract procedure appears to be safe and effective and may be routinely considered for complex anal fistula.Another technique,the anal fistula plug,derived from porcine small intestinal submucosa,is safe but modestly effective in long-term follow-up,with success rates varying from 24%-88%.The failure rate may be due to its extrusion from the fistula tract.To obviate that,a new designed plug(GORE BioA ) was introduced,but long term data regarding its efficacy are scant.Fibrin glue showed poor and variable healing rate(14%-74%).Fi La C and video-assisted anal fistula treatment procedures,respectively using laser and electrode energy,are expensive and yet to be thoroughly assessed in clinical practise.Recently,a therapy using autologous adiposederived stem cells has been described.Their properties of regenerating tissues and suppressing inflammatory response must be better investigated on anal fistulae,and studies remain in progress.The aim of this present article is to review the pertinent literature,describing the advantages and limitations of new sphincterpreserving techniques.